Perspective of Gen-Z Leadership Style in Financial Reporting and Corporate Decision Making - Hirman, Akhmad Akram (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2024)
Leadership is the process of influencing others to cooperate in achieving a common goal with a willingness to lead. There are various differences in leadership perspectives. Therefore, this research was conducted to understand the perspective of leadership style. This study aims to describe the perspective of Generation Z's leadership style in making financial statements and decision making in a company. In collecting data, this research uses interview instruments with ten sources through a case study research approach to leadership perspectives in certain companies. This research can provide new insights or more understanding of the current generation z leadership style. The results showed that most generation Z applied democratic and situational leadership styles in the company